Contraceptive discontinuation and switching in urban Istanbul region in Turkey. Issue 1 (6th February 2021) - Kurutas, Sebahat; Sato, Ryoko; Huber‐Krum, Sarah; Baykal, Simay Sevval; Rohr, Julia; Karadon, Duygu; Kaur, Navdep; Okcuoğlu, Bahar Ayca; Esmer, Yılmaz; Canning, David; Shah, Iqbal
Abstract: Objective: To evaluate rates of contraceptive discontinuation and method switching and examine their determinants in Istanbul, Turkey, because discontinuation of modern contraception leading to unintended pregnancy is a public health concern. Methods: We conducted a cross‐sectional household survey between March and June 2018 among 4224 married women of reproductive age (16–44 years). Information on contraceptive use and discontinuation for the 31 months preceding the survey was recorded in a monthly calendar. Using single and multiple decrement life‐table methods, we calculated the overall discontinuation and the cause‐specific discontinuation rates. Results: The 12‐month overall discontinuation rate was 12.32%. Intrauterine devices had the lowest discontinuation rate (7.12%). The most common reasons for discontinuation were the desire to become pregnant (6.56%) and method failure (2.76%). One in three episodes of discontinuation was not followed by method switching (32.16%). Age, education, and the method type were predictive of contraceptive discontinuation. Conclusion: To reduce method failure, women should be provided with information about method effectiveness, correct use of methods, and what to do if they anticipate their method failed (e.g., emergency contraception). Programs should focus on improving knowledge about discontinuation and method failure. Contraceptive counseling should also emphasize timely switching to an effective method after discontinuation. Synopsis: Women should be provided with information about method effectiveness and the correct use of methods to reduce method failure.